Pengaruh Kesadaran Wajib Pajak, Modernisasi Administrasi Perpajakan, Sanksi Pajak dan Keadilan Perpajakan Terhadap Kepatuhan Wajib Pajak (Studi Empiris Pada Pemilik Umkm di Kelurahan Cimone, Kecamatan Karawaci, Kota Tangerang) - One Berkat Harapan Gulo (eCo-Fin, 2021)
The importance of the role of taxes to support the progress of the nation and national development. This study was conducted to analyze the factors that affect taxpayer compliance, the independent variables used in testing MSME taxpayer compliance are taxpayer awareness, modernization of tax administration, tax sanctions and tax justice for business actors who carry out micro, small and medium business activities. registered in the Cimone sub-district, Karawaci district, Tangerang city. This study uses quantitative methods, collecting data through the distribution of questionnaires directly to MSMEs in Cimone Village, Karawaci District, Tangerang City. The sampling technique used in this research is the purposive sampling technique and the slovin method so that the samples that will be used are those included in the criteria: 1) MSME entrepreneurs who have income < 4.8 billion per year, 2) MSME actors who have a TIN, 3) do activity. Data analysis techniques are descriptive statistics, instrument testing, classical assumption testing, and multiple linear regression which are processed using SPSS version 25 software. The conclusion from the results of this study partially is that taxpayer awareness, modernization of tax administration, tax sanctions and tax justice have a significant effect on taxpayer compliance